2013
DOI: 10.1292/jvms.12-0367
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness between Host Species and Genotype of Beak and Feather Disease Virus Suggesting Possible Interspecies Cross Infection during Bird Trade

Abstract: ABSTRACT. Beak and feather disease virus (BFDV) is a causative agent of psittacine beak and feather disease (PBFD), which shows a characteristic feather disorder in psittacine birds. In the present study, the subclinical infection rate of PBFD in imported and domestically bred psittacine birds was investigated by polymerase chain reaction. As a result, 126 of 402 birds (31.3%) were found to be BFDV positive. The DNA sequences of the part of open reading frame (ORF) C1 were determined for 16 BFDV-positive rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Given that Cacatua was the genus from which PBFD was first described, 11 species of which have proven to be susceptible to BFDV infection, to date, there has been very little research on BFDV/PBFD in areas of Southeast Asia to which many of these species are native. The virus has been found in specimens from both wild and captive populations in Indonesia, a country that contains many psittacine breeding farms [ 58 ] and is heavily exploited for both the legal and illegal trapping and export of companion birds for the pet trade [ 41 ]. Equally, with high levels of parrot endemicity in South and Central America, it is surprising that no studies have been published on BFDV or PBFD incidence in wild populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Cacatua was the genus from which PBFD was first described, 11 species of which have proven to be susceptible to BFDV infection, to date, there has been very little research on BFDV/PBFD in areas of Southeast Asia to which many of these species are native. The virus has been found in specimens from both wild and captive populations in Indonesia, a country that contains many psittacine breeding farms [ 58 ] and is heavily exploited for both the legal and illegal trapping and export of companion birds for the pet trade [ 41 ]. Equally, with high levels of parrot endemicity in South and Central America, it is surprising that no studies have been published on BFDV or PBFD incidence in wild populations.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, with high levels of parrot endemicity in South and Central America, it is surprising that no studies have been published on BFDV or PBFD incidence in wild populations. Only two studies have been conducted on captive individuals originating from these geographical regions: one from Costa Rica [ 59 ] and another that included specimens of Guyanese origin [ 58 ]. Whilst one study from Brazil did not specify whether the individuals studied were of captive or wild origin and were therefore not included in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate significant differences in PBFDV infection rates among the different sample sources. Particularly noteworthy is the high infection rate observed in pet shops, which is not surprising, considering that traded birds are often key vectors for transmission of PBFDV across borders [ 11 , 24 , 25 ]. Furthermore, pet shops or breeding houses serve as hubs that gather a large number of imported or trafficked birds from diverse origins, creating environments conducive to the mixing and spread of pathogens [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growing global demand for captive birds has led to an increase in international bird trade, which has become a significant factor in the widespread dissemination of both PBFDV and BFDV, affecting both captive and wild birds [ 17 , 24 26 ]. For instance, studies have revealed a close link between PBFDV transmission and bird trade patterns through phylogeographic and phylogenetic analysis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The viral genome is a circular single-stranded DNA with a size of approximately 2 kb and contains two major open reading frames (ORFs) (ORF1 and ORF2) that encode the viral replication-associated protein Rep and the major structural capsid protein CP. BFDV is specific for members of the Psittacidae and causes psittacine beak and feather disease (PBFD), which is characterized by abnormally shaped feathers and beak in chronic forms and sudden death in acute forms ( 1 3 ). BFDV has been found worldwide and has been detected in a large variety of bird species ( 4 6 ).…”
Section: Genome Announcementmentioning
confidence: 99%